Seroprevalence of Taenia solium and Trichinella spiralis among Humans and Pigs in Ghana. (8th October 2021) - Addo, Henry Ofosu; Majekodunmi, Ayodele O.; Sampane-Donkor, Eric; Ofosu-Appiah, Lawrence Henry; Opare, David; Owusu-Okyere, Godfred; Amegah, Kingsley Ebenezer; Bimi, Langbong
Abstract : In this study, the seroprevalence of the intestinal worms Taenia solium and Trichinella spiralis in humans and pigs was assessed. A cross-sectional serological study design was performed. Blood samples were collected from 322 humans and 245 pigs used in the study. These were tested for markers of antibodies for Taenia solium and Trichinella spp. Demographic data such as sex, age, education, pig farming practices, and water source used were also obtained. An overall seroprevalence of 3.1% was recorded for Taenia solium in humans. There was also a statistical association between pig management system employed by pig farmers and seropositivity to Taenia solium (p = 0.005 ). Factors such as mode of waste disposal (p = 0.003 ) and water source used statistically correlated with Taenia solium seroprevalence among humans. For the pig samples, a Taenia solium seroprevalence of 24.9% was recorded. All the pig samples which tested positive for Taenia solium were reared on the free-ranged system. This study also recorded a seroprevalence of 0.31% for Trichinella spp. for humans and a seroprevalence of 4.5% for Trichinella spp. for pigs. Again, all the samples that showed serological evidence of Trichinella spp. among pigs came from those pigs which were raised on the free-ranged system. Proper pig management practice is a very important tool for controlling these intestinal parasites in both humans and animals. This study recommends public health education among the general public and good pig farming practices.